Dietary astaxanthin improved the body pigmentation and antioxidant function, but not the growth of discus fish (Symphysodon spp.). (24th October 2016) - Song, Xuelu; Wang, Lei; Li, Xiaoqin; Chen, Zaizhong; Liang, Gaoyang; Leng, Xiangjun
Abstract: To assess the effects of dietary astaxanthin on the growth and body colour of red discus fish ( Symphysodon spp.), synthetic astaxanthin was added into the basal diet (beef heart hamburger) with the levels of 0 (control diet), 50, 100, 200, 300 and 400 mg kg −1 respectively. The six experimental diets were fed to discus fish with an initial body weight of 10.3 ± 0.8 g for 8 weeks. The results showed that the supplementation of 50–200 mg kg −1 astaxanthin had no significant effects on growth performance of discus fish, but the high supplementation of astaxanthin (300 or 400 mg kg −1 ) significantly reduced the weight gain and increased the feed coefficient ratio ( P < 0.05). After 4 or 8 weeks of feeding, the L* (lightness) values in astaxanthin‐supplemented groups were significantly lower, while a* (redness), b* (yellowness) and skin astaxanthin contents were significantly higher than the control group ( P < 0.05). When the astaxanthin supplementation reached 200 mg kg −1, skin redness and astaxanthin contents remained relatively stable. When b* was relatively stable, the supplemental astaxanthin was 300 (4 weeks) and 50 mg kg −1 (8 weeks) respectively. With the supplemental astaxanthin increasing, the astaxanthin retention rate significantly decreased and hepatic total antioxidant capacity was strengthened. The dietary astaxanthin also significantly increased the reduced glutathione level ( P < 0.05) when the astaxanthin inclusion was higher than 50 mg kg −1 . The above results showed that dietary astaxanthin could effectively improve the skin pigmentation of red discus fish in 4 weeks and the supplementation level was suggested to be 200 mg kg −1 .